Service Quality Analysis to Increase Customer Satisfaction at BP Gas Stations in the Jabodetabek Area - Fahira, Alyssa Nur; Jovita Adeline; Sopice Selfina Kehek (Journal of Current Research In Multidisciplinary, 2023)
This research aims to determine service and facility variables that influence purchasing motivation. The population used in this research were respondents who had filled their vehicles with gasoline. The method used in collecting samples is a quantitative method, and the survey is distributed via Google Form as a survey medium. The sampling technique used is a non-probability sampling technique. The respondents selected in this study were those who had visited and filled up on gasoline, and the total number of respondents collected reached 32. After the respondents were collected, the researcher carried out several stages of analysis required in this research, namely: Gap 5 Analysis and Importance Performance Analysis (IPA). From the data obtained and the analysis that has been carried out using Gap 5 analysis calculations based on 10 indicators, this research can conclude: Quadrant I contains items or indicators that have high importance but low performance; Quadrant II contains items or indicators that have high importance and also high performance; Quadrant III contains items or indicators that have low importance and also low performance; and Quadrant IV contains items or indicators that have low importance but high performance.